Bi-functional Metasurface Based Wideband Cross-Polarizer and Narrowband Absorber - Manoj N.; Singh S.; Kumar N.; Bhattacharyya S.; Agrahari R. (My University, 2025)
A thin, compact bi-functional metasurface for wideband cross-polarization conversion (CPC) and narrowband absorber has been reported in this paper. The proposed metal-dielectric-metal layer meta-atom contains circular split rings and four L-shaped metal strips on the top layer, FR-4 substrate in the middle layer, and the copper ground plane on the bottom layer. A wide band cross-polarization conversion from 12.8 to 24.7 GHz and narrow band absorptance from 30.5 to 31.2 GHz has been observed with the designed metasurface. Both functions of the metasurface are angularly stable for the incident plane wave up to 20°. © 2023 IEEE.